COMPARING SCIENCE VIRTUAL AND PAPER-BASED TEST TO MEASURE STUDENTS' CRITICAL THINKING ON LIVING THING AND ENVIRONMENTAL SUSTAINABILITY - Rosyidah, Tiyas Hani (2016)
This research was comparing science virtual and paper-based test to measure students' critical thinking on living thing and environmental sustainability based on gender, VAK (Visual-Auditory-Kinesthetic) learning style, and students' experience. Quasi experiment method with one group post-test only design was implemented in order to analyze the data. The data population were all eighth grade students in ten classes of one of junior high school in Bandung. There were 40 eight grade students taken as the sample randomly. The quantitative data was obtained through 26 multiple choice questions constructed based on the eight elements of Inch's critical thinking and be provided in science virtual and paper-based test. The data were analyzed using statistics specifically for normality and homogenity. All data showed Asymp sig. which is less than 0.05. So, it can be inferred that all data were not homogent and distributed normally. It supposed to use nonparametric statistical analysis. The result analysis indicated that in general, science virtual test showed significantly higher score than paper-based test which signed by Asymp Sig. 0.006. In contranst, Asymp sig. showed in classification of gender, learning style, and students' experience were 0.172, 0.059, and 0.345. It indicated that there are no significant difference between science virtual and paper-based test for those three classification. All results were supported by quistionnaire about students responds on science virtual test which showed 3.47 in scale of 4. Means that the students' respond toward science virtual test tends to positive in the aspect of interest, impression, and expectation.;---Penelitian ini membandingkan tes virtual sains dan tes berbasis kertas untuk mengukur keterampilan berpikir kritis siswa berdasarkan jenis kelamin, gaya belajar VAK (Visual- Auditory - Kynesthetics), dan pengalaman siswa dalam menggunakan tes berbasis komputer. Metode quasi experiment dengan desain post tes group tunggal telah digunakan dalam penelitian ini untuk keperluan pengambilan data. Populasi dalam penelitian ini adalah seluruh siswa kelas delapan yang terbagi dalam sepuluh kelas pada salah satu SMP negeri di Bandung. Satu kelas yang terdiri dari 40 siswa dipilih secara acak untuk kemudian digunakan dalam pengambilan data. Data kuantitatif dalam penelitian ini diperoleh dengan menerapkan 26 soal pilihan ganda yang disusun berdasarkan delapan elemen berpikir kritis yang telah dikembangkan oleh Inch pada 2006 yang disajikan dalam bentuk tes virtual sains dan tes berbasis kertas. Data yang diperoleh kemudian dianalisis menggunakan statistik untuk memperoleh data normalitas dan homogenitas. Semua data menunjukkan Asymp Sig kurang dari 0,05 sehingga diklasifikasikan sebagai data yang tidak homogen dan tidak berdistribusi normal sehingga harus menggunakan uji statistik non- parametrik. Perbandingan secara umum menunjukkan perbedaan yang signifikan antara test virtual saind dan tes berbasis kertas yang diindikasikan dengan Asymp. Sig 0.006. Sedangkan Asymp Sig yang ditunjukkan oleh klasifikasi jenis kelamin, gaya belajar, dan pengalaman siswa berturut- turut menunjukkan 0,172, 0,059, dan 0,345. Hal ini menunjukkan bahwa ketiga klasifikasi tersebut tidak menunjukkan adanya perbedaan yang signifikan antara test virtual sains dan test berbasis kertas. Semua hasil tersebut didukung oleh kuisioner tentang respond siswa dalam implementasi tes sains virtual yang menunjukkan 3,47 pada skala 4 yang menunjukkan respond positive pada aspek ketertarikan, kesan, dan ekspektasi.